FLORÍSTICA, ESTRUTURA E DINÂMICA EM UMA FLORESTA OMBRÓFILA MISTA NO NORTE DO ESTADO DE SANTA CATARINA - Cubas, Rafael (2011)
The floristic composition, horizontal structure, diametrical distribution and the dynamics (ingrowth, increment, mortality) were evaluated in a remaining of a Ombrophyllous Mixed Forest, located in the National Forest of Três Barras, Três Barras City, Santa Catarina State, within a period of 5 years (2004-2009). In 2004, it were installed and measured 26 permanent plots, each one with 1 ha of area. These plots were subdivided into 10 m x 50 m (0.05 ha) adding up to 20 subunits by plot and a total of 520 subunits. In 2009 these plots were remeasured, and in both occasions, all trees with 1,3 m of diameter (DAP) equal or superior to 10 cm were measured, botanically identified, numbered and positioned according to the coordinates X,Y. It were found 18,977 boles and 18,754 trees (721.30 trees/ha) in 2004, and 18,649 boles and 18,427 trees (708.73 trees/ha), in 2009. In both measurements it were identified 72 species belong to 30 families and 53 genus. The diversity index of Shannon (H`), Simpson (C) and Pielou equability index (J), indicated that the studied area has a high floristic diversity and homogeneity. According to the hytosociologic parameters of horizontal structure, Araucaria angustifolia (Bertol.) Kuntze, Ocotea porosa (Nes & Mart.) Barroso, Cupania vernalis Cambess., Ocotea puberula (Rich.) Nes, Ilex paraguariensis A. St-Hil., Cinnamomum vesiculosum (Ness) Kostem., Syagrus romanzoffiana (Cham.) Glassman, Jacaranda micrantha Cham., Clethra scabra Pers. e Myrcia rostrata DC. are the most important species in the forest under study. As expected, the forest presented a decreasing diametric distribution. The periodic annual increment in diameter was 0.27 cm/year. The basal area was 31.14 m?/ha in 2004, and 33.49 m?/ha in 2009, with an average increment of 0.47 m?/ha/year. The annual mortality rate of the arboreal individuals was 2.14% and the annual rate of ingrowth, 2.01%. The results, notably from the basal area, indicate that the forest continue growing to reach its full stock and consequently its maturity.